EFFORTS FOR IMPROVING GOD'S GRACE OF SUPREME HADIS USING METOE PEER LESSONS - Zul Azmi (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This research is motivated by the low ability of students to understand and apply the hadith position about the favor of Allah and how to give thanks. This class action research strives toincrease the learning of the existence of hadith about the favor of God and how to give thanks to it using the peer lessons learning method of class XII PK PI 1 MAN 2 Padang Panjang City. This type of research is classroom action research. The subjects of this study were class XII PK PI 1 students, amounting to 17 people. This research was conducted in two cycles. Each cycle carried out the stages of learning: (1) planning; (2) actions; (3) observation; and (4) reflection. The research instruments used, such as (a) performance tests; (b) observation. Research data in the form of performance tests, teacher actions, and student actions. Data analysis techniques used quantitative and qualitative data analysis The results of the study illustrate that the learning methods of peer lessons can improve the ability of the analysis of the hadith about the favor of God and how to give thanks to students in class XII PK PI 1 MAN2 Padang Panjang City that is 90.29%.